З історії речовинних найменувань (суфікс -иво в українській мові) - Меркулова, Оксана; Merkulova, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Описано становлення та функціонування іменникових лексико-словотвірних типів на -иво від праслов’янської доби до сьогодення, визначено рівень продуктивності цього афікса у творенні назв із речовинною семантикою упродовж усіх періодів розвитку української мови, виявлено його валентність із твірними основами, визначено його основні словотвірні можливості. This paper describes the formation and functioning of the lexical and word-formative types of –ivo nouns within the period from the Slavonic era to the present day, determines the level of productivity of this affix in the formation of material names throughout the development of the Ukrainian language. The records examined suggest that a group of nouns referring to materials was formed in Common Slavic period, and the bulk of these substantives are verbal derivatives, which name the food; denominatives were few. The analyzed the OldRussian-Ukrainian and the Middle-Ukrainian texts, except for a few inherited derivatives, sporadically record new words. The above sources of the new Ukrainian language evidence a slight increase in the activity of the suffix -ivo: the texts dating back to the end of the XVIII – beginning of the XXI century document the vocabulary known from the Common Slavic and the Old-Russian-Ukrainian periods. In the process of formation of new words this formant affixes, as before, mainly to the verbal stems, and serves mostly to name the materials based on their chemical or physical properties, and food items.
From the History of Material Names (suffix -ivo in the Ukrainian language)
Keywords: суфікс; формант; іменники середнього роду; іменники з речовинним значенням; праслов’янська мова; давньоруськоукраїнська мова; середньоукраїнська мова; нова українська мова; suffix; formant; neuter noun; nouns with material meaning; the Proto-Slavic language; the modern Ukrainian language; the ancient Russian-Ukrainian language; the Middle-Ukrainian language